A second riboflavin import system is present in flavinogenic Streptomyces davaonensis and supports roseoflavin biosynthesis. Issue 2 (6th May 2021) - Schneider, Carmen; Mack, Matthias
Abstract: The antibiotic roseoflavin is produced by Streptomyces davaonensis in the stationary phase of growth. To support biosynthesis of the secondary metabolite roseoflavin, S. davaonensis underwent several genetic adaptations with regard to metabolism of the roseoflavin precursor and primary metabolite riboflavin. In addition to 17 riboflavin biosynthesis genes at different chromosomal locations, S. davaonensis contains the riboflavin transporter gene ribM being part of the riboflavin biosynthetic operon ribE1MAB5H . Deletion of this operon generated riboflavin auxotrophic S . davaonensis strains. The finding that S. davaonensis Δ ribE1MAB5H was able to grow in a culture medium containing low levels of riboflavin indicated that in addition to RibM, a second riboflavin transporter is present in this bacterium. The S. davaonensis genes ribXY (former rosXY ) represented candidate genes for such a second riboflavin transport system and the results of our experiments now show that RibXY from S. davaonensis is a highly efficient riboflavin importer but not a roseoflavin importer. Abstract : Streptomyces davaonensis synthesizes the antibiotic roseoflavin from riboflavin (vitamin B2 ). The genes ribXY are strongly co‐expressed with rosB encoding the key enzyme of roseoflavin biosynthesis. Our data show that RibXY is a riboflavin importer. We propose that RibXY supports roseoflavin biosynthesis by taking up the precursor riboflavin present in the environment. RibXY also may contribute to the antibiosis strategy of S . davaonensis by depleting riboflavin from the environment.